Spatial profiles of perfluoroalkyl substances and mercury in fish from northern Lake Victoria, East Africa. (December 2020) - Arinaitwe, Kenneth; Koch, Arne; Taabu-Munyaho, Anthony; Marien, Karsten; Reemtsma, Thorsten; Berger, Urs
Abstract: There is an acute deficit of data on per- and polyfluoroalkyl substances (PFASs) and mercury (Hg) in the open waters of Lake Victoria, East Africa, relative to nearshore areas. We analyzed stable isotopes (δ 15 N and δ 13 C), PFASs and Hg in Nile Perch and Nile Tilapia muscle and liver samples from nearshore and open lake locations from the Ugandan part of the lake. The δ 15 N values of Nile Perch muscle indicated a higher trophic level for samples from the open lake than from nearshore locations. Averages of ∑PFAS concentrations in Nile Perch muscle and liver (0.44 and 1.75 ng/g ww, respectively) were significantly higher than in Nile Tilapia (0.24 and 0.50 ng/g ww, respectively). ∑PFAS concentrations in muscle of open lake Nile Perch were significantly higher than for nearshore samples. A similar observation was made for total mercury concentrations in muscle (THg_Muscle ) of Nile Perch. THg was dominated by methyl mercury (MeHg +, 22–124 ng/g ww) and mercuric mercury (Hg 2+, <MDL-29 ng/g ww) in Nile Perch muscle. Strong correlation between MeHg + and some PFASs (e.g. PFOS: r  = 0.704, P  = 0.016) suggested similar exposure routes or factors. Estimated human daily intake values of PFOS from fish consumption were below international limits whereas for MeHg +, the US EPA reference dose was exceeded. Graphical abstract: Image 1 Highlights: Fish samples from the open lake were at higher trophic level than nearshore samples. Trophic magnification is a key factor in the PFASs and MeHg + spatial profiles. There was significant correlation between MeHg + and some PFASs in fish muscle. There was no significant correlation of concentrations to sex, length or weight of fish. Concentrations and estimated human exposure are below international tolerable limits.